Novel method of constructing the zero-sum distinguishers - Le DONG; Wen-ling WU; Shuang WU; Jian ZHOU (Tongxin xuebao)
A novel method of constructing the zero-sum distinguishers for AES-like permutations was proposed by considering the diffusion properties of these permutations,which have the similar construction.The method combined the higher-order integral attack and the higher-order differential attack.Utilizing the selected intermediate-state-structure whose active mode was determined,a higher-order integral path was constructed.Then,a higher-order differential trace was built from the two ends of the integral path.Applying the method,the full-round zero-sum attack on two permutations adopted by the PHOTON family was improved.Besides,a 31.5-round zero-sum distinguisher of the core function of JH hash function was constructed,which entered into the final round of the SHA-3 competition.